2008
DOI: 10.1094/pdis-92-6-0947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soybean Germplasm for Resistance to Soybean Rust (Phakopsora pachyrhizi) in Nigeria

Abstract: Soybean rust, caused by Phakopsora pachyrhizi, is one of the most important constraints to soybean production worldwide. The absence of high levels of host resistance to the pathogen has necessitated the continued search and identification of sources of resistance. In one set of experiments, 178 soybean breeding lines from the International Institute of Tropical Agriculture were rated for rust severity in the field in 2002 and 2003 at Ile-Ife, Yandev, and Ibadan, Nigeria. Thirty-six lines with disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
2
40
0
2
Order By: Relevance
“…The GGE biplot was used to identify disease resistance and associated stability in several crops, such as soybean (Twizeyimana et al, 2008), chick pea (Sharma et al, 2012), wheat (Gitonga, Ojwang, Macharia, & Njau, 2016), mung bean (Alam, Somta, Jompuk, Chatwachirawong, & Srinives, 2014) and rice (Idowu, Salami, Ajayi, Akinwale, & Sere, 2013;Tabien, Samonte, Abalos, & San Gabriel, 2008). Moreover, genotype and GE interaction, graphically represented using a GGE biplot to assess the genotypes and environment, play an important role in variety selection (Yan, 2001;Yan & Hunt, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The GGE biplot was used to identify disease resistance and associated stability in several crops, such as soybean (Twizeyimana et al, 2008), chick pea (Sharma et al, 2012), wheat (Gitonga, Ojwang, Macharia, & Njau, 2016), mung bean (Alam, Somta, Jompuk, Chatwachirawong, & Srinives, 2014) and rice (Idowu, Salami, Ajayi, Akinwale, & Sere, 2013;Tabien, Samonte, Abalos, & San Gabriel, 2008). Moreover, genotype and GE interaction, graphically represented using a GGE biplot to assess the genotypes and environment, play an important role in variety selection (Yan, 2001;Yan & Hunt, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that smaller values for LD and LF are characteristic of partial resistance (Wang & Hartman, 1992;Twizeyimana et al, 2008). In the current study, it has been shown for the first time that the M-5 clone, which had the lowest measures of disease intensity during the entire experiment, possibly possesses partial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Significant yield loss occurs on early infected soybean crops than late infection. Severe infection significantly reduces the yield up to 80% (Twizeyimana et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the susceptibility of resistant cultivars are durability of the resistance to ASR which is easily broken due to pathogen variability (Oliveira et al 2005), the complexity of genes that controls resistance to ASR, and environmental factors (Garcia et al 2008). Thus, tolerant cultivars are more reasonable for ASR integrated control (Twizeyimana et al 2008). Tolerance can be defined as plant capacity to resist pathogen infection and development, without significant reduction in yield or quality of the product (Schafer 1970).…”
Section: Introductionmentioning
confidence: 99%